Implementation of the quality management system in the enterprise producing bentonite clay - Kulisz, M.; Zhumabekova, J.D.; Firsova, E.B.; Aubakirova, Z.; Zhairbaeva, G. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2022)
In the developed countries of the world, the problem of quality improvement occupies a leading place in ensuring the competitiveness of products and services, building new relationships between consumers and producers, and meeting material needs, social interests, and spiritual demands, especially in production and industrial engineering. With the entry of Kazakhstan enterprises into international markets and the opening of the Kazakh market for the goods of foreign firms, the problem of product quality has become a priority for domestic producers. Currently, there are problems in the implementation of the quality management system in Kazakhstan. Accordingly, the article discusses the problems of implementing a quality management system in the example of a company producing bentonite clay in Kazakhstan. The methods of observation, analysis, and synthesis, as well as the technique of interview with the head of the quality group, were used for the research. As a result of the research, the management system introduced in this enterprise was discussed, and the problems observed during the system implementation were presented, as well as recommendations for the company.